Analisis Wacana Multimodal Pada Gambar Iklan Nugget Kanzler Versi Nicholas Saputra Di Instagram - Futi Hamdiyah; Khanaya Shalsabilla; Khadavi Khadavi; Mustika Wati Siregar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to analyze the multimodality of Nicholas Saputra's version of Kanzler nugget advertising images on Instragram. This research uses a qualitative descriptive method. Data collection techniques in the form of documentation and data sources from Instagram Kanzler's friends describe Nicholas Saputra as Brand Ambrasador. The data analysis technique uses Kress and Leeuwen's theoretical concepts. The results of this research are that by integrating these three aspects, Nicholas Saputra's version of the Kanzler nugget advertisement succeeded in creating a strong visual appeal, conveying the message effectively, and building friendly relationships with consumers.